CD44 Glycosylation as a Therapeutic Target in Oncology - Liao, Chengcheng; Wang, Qian; An, Jiaxing; Chen, Jie; Li, Xiaolan; Long, Qian; Xiao, Linlin; Guan, Xiaoyan; Liu, Jianguo (Frontiers in Oncology, 2022)
The interaction of non-kinase transmembrane glycoprotein CD44 with ligands including hyaluronic acid (HA) is closely related to the occurrence and development of tumors. Changes in CD44 glycosylation can regulate its binding to HA, Siglec-15, fibronectin, TM4SF5, PRG4, FGF2, collagen and podoplanin and activate or inhibit c-Src/STAT3/Twist1/Bmi1, PI3K/AKT/mTOR, ERK/NF-κB/NANOG and other signaling pathways, thereby having a profound impact on the tumor microenvironment and tumor cell fate. However, the glycosylation of CD44 is complex and largely unknown, and the current understanding of how CD44 glycosylation affects tumors is limited. These issues must be addressed before targeted CD44 glycosylation can be applied to treat human cancers.